Will the DSM Strategy Spur Innovation? - Andrea Renda (Intereconomics, 2017)
In summary, the DSM strategy appears laudable and overall very comprehensive. However, its impact will depend on whether the Commission manages to create a more suitable environment for innovation and entrepreneurship by upgrading skills, promoting more adaptive rulemaking, empowering end user choice, and avoiding rules that are hostile to innovation, such as excessive restrictions to text and data mining and the extension of obsolete rules to OTTs.
Keywords: 330